HACKING THE ART OF EXPLOITATION - ERICKSON JON; ERICKSON (SAN FRANCISCO NO STARCH PRESS, 2008)
HACKING THE ART OF EXPLOOTATION . COMPUTER SECURITY, COMPUTER HACKERS
COMPUTER SECURITY
AIML AND DS
Keywords: ERICKSON JON; COMPUTER HACKING; HACKING